2015
DOI: 10.15805/addicta.2017.4.2.0015
|View full text |Cite
|
Sign up to set email alerts
|

Programs for Preventing Internet Addiction during Adolescence: A Systematic Review

Abstract: With the Internet having become an inevitable part of life, Internet addiction, being on the agenda, is viewed as a significant problem for adolescents and is frequently a subject of research. One observes that in addition to studies on the prevalence of Internet addiction during adolescence and its relation to different variables, efforts to prevent Internet addiction in adolescence in recent years have particularly started to gain importance. The number of studies on preventing Internet addiction has been ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…We know that a better understanding of any issue in digital society research requires new, reliable, and valid instruments which provide more accurate information to differentiate normal from problematic use, as well as to distinguish the types of risks that require psychological attention from risks that can be addressed and prevented through digital safety education. This validated scale is therefore a useful tool for defining actions in the fields of education, family, and social life [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], which can help to reduce the exposure of adults to risks that are becoming more frequent due to the increase in daily Internet use time. This usefulness is based on the need raised by Dönmez et al [ 29 ], who pointed out that society frequently demands that policymakers assess the risks of technologies and manage them appropriately in social integration processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that a better understanding of any issue in digital society research requires new, reliable, and valid instruments which provide more accurate information to differentiate normal from problematic use, as well as to distinguish the types of risks that require psychological attention from risks that can be addressed and prevented through digital safety education. This validated scale is therefore a useful tool for defining actions in the fields of education, family, and social life [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], which can help to reduce the exposure of adults to risks that are becoming more frequent due to the increase in daily Internet use time. This usefulness is based on the need raised by Dönmez et al [ 29 ], who pointed out that society frequently demands that policymakers assess the risks of technologies and manage them appropriately in social integration processes.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the studies showed a direct relationship between advances in technology and the risks of digital society due to technology use, as well as a lack of instruments to provide an accurate diagnosis of the situation. In response to this social concern, various initiatives and programs have emerged and been developed to educate and prevent risk in the general population [ 34 , 35 ]. One recent initiative in Spain is the project, “Development and Optimization of Intergenerational Educational Activities to Promote Responsible Internet Use” (“Desarrollo y optimización de acciones educativas intergeneracionales para la promoción del uso responsable de Internet” (EduACD)), performed during 2020–2022 to foster training actions for citizens.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging technologies have a huge impact on the way we live, learn and interact. Technology will be one of the main human needs in helping and improving the efficiency of human activities (Bagatarhan & Siyez, 2017).…”
Section: Animation In Educationmentioning
confidence: 99%
“…Fifteen intervention studies were included in the review, but due to the heterogeneity of their scope, content, outcome evaluation, and assessment tools used, the findings regarding the effectiveness of the programs remained inconclusive. The second review (Bağatarhan & Siyez, 2015) focused on the effectiveness of prevention programs for internet addiction during adolescence, drawing on multiple research databases in Turkish and English. Of the 435 articles found, only 5 met the inclusion criteria.…”
Section: Prevention Programs For Piumentioning
confidence: 99%